Leadership for learning in technology-rich upper secondary school classrooms - Kjell Atle Halvorsen (Universitetsforlaget, 2017)
Abstract The article analyses strategies for classroom leadership in technology rich upper secondary classrooms, arguing that such strategies can involve technical, organizational, didactic and relational involvement elements. It suggests that these elements can be captured in an interactive, ecological model of classroom leadership. The findings are discussed in the light of theories on leadership as distributed influence, the classroom as a collaborative community of practice, and learning as collaborative, multimodal knowledge creation.